Application of Blockchain Technology for Information Security Risk Management in the Electronic Banking System - O. V. Aseev; M. D. Sayymova; E. A. Bogdanova (Вестник Северо-Кавказского федерального университета, 2023)
Introduction. The article examines the essence of Blockchain technology and the possibilities of its application in the banking sector. The most promising directions for the development of blockchain technology are specified. The basic principles are described, as well as potential risks associated with the safety of using this technology. The relevance of this topic is due to the fact that interest in this technology has increased in the scientific community, which is not surprising, because blockchain reduces the time spent on banking transactions, makes transactions safe and transparent. Goal. The purpose of this article is to analyze the functionality and effectiveness of using blockchain technology to ensure the security of banking operations.Materials and methods. The research employs the methods of scientific cognition: empirical research (comparison, collection and study of data), comparative research, synthesis of theoretical and practical material. The sources of methodological information are scientific publications related to the subject under study.Results and discussion. To achieve the goal, the main tasks were identified, namely: to study the theoretical basis, to identify the advantages and disadvantages of the technology, as well as to analyze the effectiveness and safety of using blockchain technology in the banking sector.Conclusion. Based on the results of the study, it can be concluded that Russian banks effectively use blockchain technology.